Suara Pemuda : Peran Media dan Teknologi Instagram bagi Komunitas Amnesty dalam Menyuarakan Hak Asasi Manusia di Universitas Jember - Nanda Aulia Rahmawati; Fierena Riza Guntari; Fauziyah Almas Janani Widodo (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Human Rights are often the main topic of problems in a region, sometimes as a society, Human Rights must always be voiced so that every individual or group gets a decent life and rights. But in some cases, especially in Indonesia, there are many news and problems where the main issue is Human Rights, from the lack of justice and humanity for some groups, in this case there needs to be an important agent for social change and balance in a country. Students who have the predicate as Agents of Change have an important role in society to continue to advocate freedom of expression and opinion. Students have many communities that are active in the field of voicing Human Rights, one of which is the Amnesty community, Amnesty is an international forum or community driven by students and almost every university in Indonesia has such a community. One of the mass media often used by the Amnesty community is Instagram. This platform is currently in demand by many generations, especially the younger generation, especially students. By using Instagram as a platform to voice Human Rights, Amnesty can attract people around and even outside those who cannot be reached to help voice Human Rights for the common good. Human Rights issues are not only within the scope of the University but also in the international realm.